CONTRAST BATH SOAKING THERAPY IMPROVES BLOOD CIRCULATION IN DIABETIC FEET - Berkah Afif Udin; Umi Faridah; Muhamad Jauhar; Faridha Alfiatur Rohmaniah (Universitas Muhammadiyah Kudus, 2025)
AbstractDiabetes Mellitus (DM) is the mother of all diseases that can